ANALISIS MANFAAT-BIAYA TEMPAT PEMBUANGAN SAMPAH AKHIR (TPA) GALUGA - Ade Jamal Mirdad; Sunyono Sunyono (Jurnal Ekonomi-Qu, 2017)
The purpose of this study was to identify direct benefits and losses in the last year for the people of Galuga Village, Dukuh Village and Cijujung Village, which arise from the existence of TPA Galuga. The method of analysis used is Benefit- Cost Ratio. Based on the results of interviews with the surrounding community, the TPA Galuga does provide benefits in the form of jobs as both collectors and garbage collectors so that they earn income to meet the needs of life. Conversely, the loss is felt by them in the form of uncomfortable air and contaminated water so they incur additional costs to minimize the negative impact. Based on the results of Benefit Cost Ratio (BCR) analysis of 6.36 indicates that the existence of TPA Galuga provides more direct benefits. it means that the direct revenue earned is greater than 6 times the direct costs incurred in the presence of the landfill.Keywords:Benefits, Cost and Final Disposal